Facilitators and barriers to implementing a social franchising model of delivering eye care services in rural China: a qualitative study using the updated Consolidated Framework for Implementation Research - Huan Wang; Xiaochen Ma; Yaojiang Shi; Xiaodong Dong; Hongyu Guan; Wenting Liu; Junling Zhao (BMJ Open, 2025)
Objectives To identify the barriers and facilitators to implementing the social franchising model ‘Smart Focus’ for delivering eye care services to children in rural China, using the updated Consolidated Framework for Implementation Research (CFIR 2.0) as a theoretical basis to evaluate implementation performance drivers and propose strategies for effective scaling and sustainability.Design This qualitative study involved semi-structured interviews with key stakeholders from both the supply side and demand side. Interview guide development, coding, analysis and reporting of findings were thoroughly informed by the CFIR 2.0.Setting Smart Focus operated in 23 poverty-designated counties across four western provinces in China, collaborating with local public hospitals, private optical shops and third-party non-governmental organisations.Participants Key informants included two Smart Focus project managers, six representatives from local education and health bureaus and ten vision centre employees and franchise operators.Results Key facilitators of implementation included a robust evidence base, high trialability and adaptability of the innovation, relative advantages over competitors, standardised resources and effective training programmes. Major barriers included challenges in cross-departmental collaboration, underestimated variable costs, competition from private providers, high employee turnover due to inadequate incentives and the lack of feedback mechanisms for contextual adaptation.Conclusions This study highlights critical barriers and facilitators to implementing social franchising models for eye care in low-resource settings. While Smart Focus demonstrated success in scalability, achieving sustainability requires addressing financial constraints, staff retention and adaptive feedback mechanisms. The findings provide a context-specific framework for scaling health innovations in low- and middle-income countries, offering valuable lessons for bridging the gap between social and business objectives in hybrid models.